Sacajawea : the story of Bird Woman and the Lewis and Clark Expedition - Bruchac, Joseph, 1942- (Hartcourt, Inc., 2000)
Young Sacajawea has been asked to join Lewis and Clark in their exploration of the American West. As a translator, peacemaker, caretaker, and guide, Sacajawea alone will make the historic journey of Lewis and Clark possible. This captivating novel, which is told in alternating points of view -- by Sacajawea herself and by William Clark -- provides an intimate glimpse into what it would have been like to witness firsthand this fascinating time in our history.